UPC-A AS A FORM OF BARCODE AND HOW MANUFACTURE MANUAL - Saepul Lukman Lukman (Majalah SIKOMTEK, 2006)
Barcode is a special code that shaped arrangement of vertical bars varying in width andinterspersed with an empty space / white space. Barcodes are used in general to give a specialmark or specific identification of the goods / items different from his own specifications.Barcodes can be read and encoded by using a tool moving / Barcode Scanner.